Improving Students' Reading Ability Using Grammar Translation Method - Afiah, Devi Siti Sihatul (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2014)
This research aims at revealing: (1) To find out whether Grammar TranslationMethod can improve the reading ability; (2) To find out the strengths and weaknesses of Grammar Translation Method.The Class Action Research was carried out in MA Salafiyah Cirebon in academic year of 2011/2012 from April to June 2012. The population was the first semester of MA Salafiyah in academic year of 2011/2012. The number of population was 22 students.The results of this research were: (1) The Grammar translation Method can Improves the students' reading ability, it can be seen in the table 1; (2) The strengths of Grammar Translation Method was the students challenged to read the difficult texts. And the weakness of Grammar Translation Method was felt bored to memorize the vocabularies and irregular verb.